Evaluation of Basal Heave Stability for Deep Excavations in Clay using the Discontinuity Layout Optimization Method - Susiyanti, Angela Dewi Maharani; Lim, Aswin (Institute of Research and Community Outreach - Petra Christian University, 2026)
clay soils, which often causes significant ground movement and threatens nearby structures. Traditional analysis methods generally assume homogeneous soil conditions and ignore the variation of strength with depth, which limits their application in complex field situations. This research investigates basal heave stability using the Discontinuity Layout Optimization (DLO) method, which identifies critical failure mechanisms by optimizing potential discontinuities in the soil mass. The research examines the influence of undrained shear strength (Su​), its gradient, and the excavation width-to-height ratio (B1​/H) on the safety factor, considering homogeneous and layered soil models. Results show that the safety factor increases with higher Su​ values but decreases as B1​/H increases. While the DLO method provides reliable predictions for homogeneous soils, but it shows limitations in layered soils. Therefore, for more accurate results in complex stratigraphy, integrating DLO with the Finite Element Method (FEM) is recommended.